Red modernism : American poetry and the spirit of communism - Steven, Mark (Hopkins studies in modernism., 2017)
"In Red Modernism, Mark Steven asserts that modernism was highly attuned--and aesthetically responsive--to the overall spirit of communism. He considers the maturation of American poetry as a longitudinal arc, one that roughly followed the rise of the USSR through the Russian Revolution and its subsequent descent into Stalinism, opening up a hitherto underexplored domain in the political history of avant-garde literature. In doing so, Steven amplifies the resonance among the universal idea of communism, the revolutionary socialist state, and the American modernist poem. Focusing on three of the most significant figures in modernist poetry--Ezra Pound, William Carlos Williams, and Louis Zukofsky--Steven provides a theoretical and historical introduction to modernism's unique sense of communism while revealing how communist ideals and references were deeply embedded in modernist poetry. Moving between these poets and the work of T.S. Eliot, Langston Hughes, Muriel Rukeyser, Gertrude Stein, Wallace Stevens, and many others, the book combines a detailed analysis of technical devices and poetic values with a rich political and economic context. Persuasively charting a history of the avant-garde modernist poem in relation to communism, beginning in the 1910s and reaching into the 1940s, Red Modernism is an audacious examination of the twinned history of politics and poetry"--